How Distant is ‘Inclusion’? A Study of Delhi School Teachers - Sharma, Yukti (INDIAN EDUCATIONAL REVIEW, 2018)
This research paper is based on the study of perceptions of school teachers undertaken as a research project*. The study explored teachers’ perception about the children with special needs and as the representation of such children in their respective schools. Also, the perception of teachers regarding inclusive spaces, practices and provisions found in their respective schools were studied. In this process, the teachers’ attitudes towards as well as preparedness for inclusion in schools were analyzed. In the light of teachers’ responses, the paper makes an attempt to present the reflections of extent of preparedness and inclusive practices in schools in the present times.